Tax payer's satisfaction towards the usage of e-filing system intention of the Inland Revenue Board of Malaysia (IRB) / Awang Sebli Awang Bojeng, Siti Nadia Zainal Abidin and Soffian Mohd Ibrahim - Awang Bojeng, Awang Sebli; Zainal Abidin, Siti Nadia; Mohd Ibrahim, Soffian (2018)
Tax as a source of revenue is a key element for country’s growth and development. The introduction of e-Filing system by IRB has helped to increase the collection of taxes since its inception in 2006. Thus, this study is conducted to examine the dimensions of taxpayers’ satisfaction and how it will influence the behavioural intentions of taxpayers in adopting e-Filing system. The dimensions of satisfaction that we have analysed are adopted from E-S-QUAL model which are efficiency, system availability, fulfilment, privacy and two new items found from qualitative survey; convenience and resource saving. Theory Reasoned Action (TRA) is used to examine the relationship between these dimensions of taxpayers’ satisfaction and their behavioural intention. The data were collected from randomly selected respondents. The findings of the study are based on questionnaire analysis. It is hoped that the findings and interpretation from this research will help IRB to improve its e-filing system. All comments and recommendations from the taxpayers will be forwarded to the management of IRB consideration.